PERFORMANCE-STRUCTURE ANALYSIS OF ELITE JUNIOR BOY TENNIS PLAYERS - DOBOS, Károly (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2018)
Introduction: Extremely complex factors lie behind sport performance in tennis. In order to evaluate the importance and weight of these factors, it is important to examine them each by each. Objective: The aim of the research was to examine the performance-structures lying behind the physical performance of elite junior boy tennis players and to analyse the relationship between the calendar year and physical variables. Method: Altogether 80 elite junior boy tennis players participated in the research. Their average age was 14.30+2.22 years. Eleven different field tests were applied. Results: Correlations were found between the calendar year age and all the physical variables, the 5-meter linear run and the agility, the explosive strength of the leg, the 5-meter sprint and the agility. The speed of serve showed correlation with the dominant-side upper limb, the upper body and the explosive strength of the leg. Furthermore, there was a correlation between the shoulder flexibility and the flexibility of the lower limb, the flexibility of the lower leg, the explosive strength of the leg and the agility, the flexibility of the shoulder and the speed of serve. Conclusions: A differentiation in the conditioning training of elite junior boy tennis players is recommended based on their age, from the age of 11, together with the joint developmental trainings of explosive strength and flexibility, agility and explosive strength of the leg, the improving of explosive strength in the lower and upper limbs, and the use of 5 meter linear run and the athletic throws as a means of training.